Collaborative cognitive content dissemination and query in heterogeneous mobile opportunistic networks - Radenkovic, Milena; Huynh, Vu San Ha (2017)
This paper investigates complex challenges of opportunistic discovery of content stored in remote mobile devices and delivery to the requesting nodes in heterogeneous mobile disconnection prone environments. We propose new latency aware collaborative cognitive caching approach suitable for content dissemination and query in heterogeneous opportunistic mobile networks and dynamic workloads. Utilising fully localised and ego networks multi-layer predictive heuristics about dynamically changing topology, dynamic resources and varying popularity content, our cognitive caching achieves high success ratio, low delays and high caching efficiency for very different real world dynamically changing mobile topologies.